دراسة مقارنة لمستوى الرضا عن الحياة للمارسين وغير الممارسين للنشاط الترويحي في لعبة كرة القدم لدى كبار السن (50-55 سنة) - ميسون, أحمد (Institut d'Éducation Physique et Sportive - Mostaganem 2023/2024, 2024)
يهدف بحثنا هذا إلى معرفة مدى تأثير ممارسة الأنشطة الترويحية الرياضية في شكل لعبة كرة القدم على الرضا عن الحياة عند كبار السن(50-55) ، ولتعزيز هذا الهدف أجرينا بحثا على مجموعة من الأفراد ممارسين وغير ممارسين للنشاط الترويحي الرياضي في لعبة كرة القدم ضمت كل مجموعة 50 فرد على مستوى بلديتي عين فراح و وادي الأبطال بولاية معسكر ، حيث اعتمدنا على المنهج الوصفي وذلك من خلال توزيع الاستبيان على جميع أفراد العينة ومن ثم جمعها و تفريغها ، وبعد تحليلنا للنتائج المحصل عليها توصلنا إلى انه هناك فروق دالة إحصائيا بين ممارسين و الغير ممارسين للأنشطة الترويحية الرياضية في الرضا الذاتي ، الأسري، الاجتماعي و المهني أما في الرضا الخاص بالخلو عن الأعراض العصبية و الميول الانسحابية فكانت النتائج سلبية أي لم تكن هناك فروق دالة إحصائيا . لذا من خلال هذه النتائج نوصي فئة كبار السن بضرورة ممارسة الأنشطة الترويحية الرياضية . // // // // // TheImpact of Recreational Sports Activities, Specifically Football, on Life Satisfaction Among Seniors (Aged 50-55)Abstract: This study aims to examine the impact ofparticipatingin recreational sports activities, particularly football, on life satisfaction among seniors aged 50 to 55. To achieve thisobjective, we conducted research on a sample consisting of two groups, each with 50 individuals, including both participants and non-participants in recreational sports activities from the municipalities of Ain Farah and Oued ElAbtalin the city of Mascara . The studyutilizeda descriptive approach by distributing a questionnaire to all sample members, collecting the data, and then processing and analyzing the results usingappropriate statisticalmethods .The resultsindicatedstatistically significant differences between participants and non-participants in recreational sports activities in terms of self-satisfaction, family satisfaction, social satisfaction, and professional satisfaction. However, regardingsatisfaction related to the absence of neurological symptoms and withdrawal tendencies, the results were negative, indicatingno statistically significant differences between the twogroups. Based on these results, we recommend that seniors engage in recreational sports activities to improve their overall life satisfaction in various aspects.
MEPS-2024-21
Keywords: مستوى الرضا عن الحياة - المارسين وغير الممارسين للنشاط الترويحي - كرة القدم - كبار السن (50-55 سنة)